The indoor environmental benefits from replacing unflued gas and portable electric heaters with higher capacity non indoor polluting heaters : an interventional field study : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Building Technology at Massey University, Manawatu campus, New Zealand - Boulic, Mikael (Massey University, 2012)
A two year intervention study investigated the relationship between domestic heaters and indoor environment of children with asthma. The main objectives of this project were to investigate the changes to the measured indoor environmental parameters, when a higher capacity non indoor polluting replacement heater was installed and to examine if this intervention was sufficient to provide the households with a healthy indoor environment. Baseline monitoring was carried out in the living rooms and child’s bedrooms of 33 homes including the real time measurement of four gaseous key pollutants, room temperature, relative humidity (RH) and usage of the original heater (unflued gas heater (UGH) or portable electric heater) for up to one week. Airborne fungi level and fungi level from the floor dust were measured and a visual inspection of fungi was undertaken. The suitability of the wall environment for fungi development was estimated via a fungal detector and correlated to wall psychrometric conditions (temperature, RH). The different fungi assessment methods were compared. The measurements were repeated in 36 homes, following the replacement of the UGH or portable electric heater with a higher capacity non indoor polluting heater such as flued gas heater, wood pellet burner or heat pump in the intervention homes. Of these homes, 27 were monitored for both winters. Excessive levels of pollutants were found when the UGH was operated, even for short periods. Acceptable air quality levels were achieved for all replacement heater homes. The study showed that the replacement heaters were operated for longer periods than the heaters they replaced. The homes with the replacement heaters installed were warmer and dryer and had less mould than the homes with UGHs. The replacement heater also had a positive impact on the wall psychrometric conditions with reduced water availability for mould to grow. Replacing the UGH with a higher capacity non indoor air polluting heater reduced the asthmatic children’s exposure to harmful indoor environment. Unvented gas heating appliances should be more regulated and ideally should not be operated in homes.
The following have been removed due to copyright restrictions: Boulic, M., Phipps, R. A., Cunningham, M., Cleland, D. J., and Fjällström, P. R. (2007). 'Too dry and too cold for mould germination in New Zealand dwellings?', International Journal of Global Environmental Issues, 7(4), 330-340. Phipps, R. A., Cunningham, M., Fjällström, P. R., Boulic, M., Howden- Chapman, P., Crane, J., Baker, M., Viggers, H., Robinson, J. A., Nicholls, S., Lloyd, B., and Chapman, R. (2006). 'Not just hot air: Methods and preliminary results for the intensive monitoring of emissions and by-products from two types of domestic heaters', Proceedings of Healthy Buildings 2006, de Oliveira Fernandes, Gameiro da Silva, and Rosado Pinto (Eds.), Lisboa, Portugal, 399- 402. Boulic, M., Fjällström, P. R., Phipps, R. A., Cunningham, M., Cleland, D. J., Howden-Chapman, P., Chapman, R., and Viggers, H. (2007). 'Cold homes in New Zealand - low heater capacity, or low heater use?' International Council for Research and Innovation in Building and Construction. Auckland, New Zealand. 1-8. Boulic, M., Fjällström, P. R., Phipps, R. A., Cunningham, M., Cleland, D. J., Pierse, N., Howden-Chapman, P., Chapman, R., and Viggers, H. (2008). 'Cold homes in New Zealand - Does increasing the heater capacity improve indoor temperatures?' Clean Air and Environmental Quality Journal, 42(3), 22-30. Boulic, M., Phipps, R. A., Cunningham, M., Cleland, D. J., and Fjällström, P. R. (2009). 'Did replacing unflued gas heaters with inverter heat pumps decrease the indoor potential for mould growth?' In 'Do damp and mould matter? Health impacts of leaky homes', Howden-Chapman, Bennett, and Siebers (Eds.) Wellington, New Zealand. 100-113. Boulic, M., Phipps, R. A., Fjällström, P. R., Cunningham, M., Cleland, D. J., and Howden-Chapman, P. (2009). 'Stop "heating the birds": Well being at home and heating options'. In Massey University Centre for Energy Research Energy Post Graduate Conference, Palmerston North, New Zealand. 1-6.
Keywords: Domestic heating; Indoor pollution; Gas heating; Unflued heating; Health effects of domestic heaters; Indoor environment